(3fJGFL GdCacGQ aj TQM GdEXgGQ ddHQcdjs - (3GdCWg dj (B( (3CVdj (B) (3GdJQcj, BWg dj, eUWai Hf MeRI Hf EHQGgje, J HYO (B1085(3g`s ((3HdOI CeGs)
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GdCdaGX bhGdH GdeYGfj haVdgG Ydi SGFQ GdCUhGJ HfXe MQha GdeHGfjs
(3BNQgG (B:s
(3hdG jLhR HfGDg dhLhO GdaUd HGdYGWa hdPG de jJYQV dg dCf cdGeg aj LGFR GdHfG hEfeG de jJYQV dMce SGFQ GdJhGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 232s
(3eYLe GdeDdajf(B: 3 / 863s
(3EjVGM Gdecfhf(B: 2 / 620s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs